Corticomotor Excitability Changes Associated With Freezing of Gait in People With Parkinson Disease - Lee, Ya-Yun; Li, Min-Hao; Tai, Chun-Hwei; Luh, Jer-Junn (Frontiers in Human Neuroscience, 2020)
Background and Purpose Freezing of gait (FOG) is a debilitating gait disorder in people with Parkinson’s disease (PD). While various neuroimaging techniques have been used to investigate the pathophysiology of FOG, changes in corticomotor excitability associated with FOG have yet to be determined. Research to date has not concluded if changes in corticomotor excitability are associated with gait disturbances in this patient population. This study aimed to use transcranial magnetic stimulation (TMS) to investigate corticomotor excitability changes associated with FOG. Furthermore, the relationship between corticomotor excitability and gait performances would be determined. Methods Eighteen participants with PD and FOG (PD + FOG), 15 without FOG (PD − FOG), and 15 non-disabled adults (Control) were recruited for this study. Single and paired-pulse TMS paradigms were used to assess corticospinal and intracortical excitability, respectively. Gait performance was measured by the 10-Meter-Walk test. Correlation analysis was performed to evaluate relationships between TMS outcomes and gait parameters. Results Compared with the Control group, the PD + FOG group showed a significantly lower resting motor threshold and reduced short intracortical inhibition (SICI). Correlation analysis revealed a relationship between resting motor evoked potential and step length, and between SICI and walking velocity in the Control group. While the silent period correlated with step length in the PD − FOG group, no significant relationship was observed in the PD + FOG group. Discussion and Conclusion Compared to the Control group, the PD + FOG group exhibited reduced corticomotor inhibition. Distinct correlations observed among the three groups suggest that the function of the corticomotor system plays an important role in mediating walking ability in non-disabled adults and people with PD − FOG, while people with PD + FOG may rely on neural networks other than the corticomotor system to control gait.